Strategizes For Parents of Mentally Retarded Children’S: Examining coping strategies and family adaptation in families with mentally retarded children (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Families which are capable of coping with having amentally retarded child are able to mobilise their internal and external meansof support to deal effectively with special needs of their child. The abilityof the family to cope with any situation will often depend on their strengthsand resources. In this study the coping strategies and mediating factorsstudied were awareness about the child’s problem, expectations and attitudes,child rearing practices, social support, and global family adaptation. Familycoping was measured using a pretested self-administered questionnaire. 74%families were seen to have adequately adapted to having a mentally retardedchild in their family, as measured on the global adaptation scale. Theremaining 26% families had inadequately adapted, of which 7% showed poor coping.